The Effect of Teachers’ Pedagogical Competence and Learning Facilities on Academic Achievement with Information Technology Usage as a Moderating Variable among Office Management Students - Novia Ainur Rohmah; Siti Sri Wulandari (Lembaga Penelitian dan Pengembangan Sumberdaya Wilayah (elrispeswil), 2026)
This study aims to examine the effects of teachers’ pedagogical competence and learning facilities on students’ academic achievement, with information technology usage as a moderating variable within the framework of Social Cognitive Theory. A quantitative explanatory research design was employed. The population consisted of 125 Office Management students, with a sample of 96 selected using proportional stratified random sampling. Data were collected through questionnaires, observations, and report card documentation, and analyzed using SEM-PLS with SmartPLS 4. The results indicate that teachers’ pedagogical competence (β = 0.596; p < 0.001) and learning facilities (β = 0.530; p < 0.001) have positive and significant effects on academic achievement. However, information technology usage negatively moderates the relationship between pedagogical competence and achievement (β = -0.155; p = 0.002), suggesting that higher technology use may weaken the direct influence of teachers, possibly due to increased learner autonomy. These findings highlight the dual role of technology in shaping learning dynamics.